A Flexi‐PEGDA Upconversion Implant for Wireless Brain Photodynamic Therapy. Issue 29 (2nd June 2020) - Teh, Daniel Boon Loong; Bansal, Akshaya; Chai, Chou; Toh, Tan Boon; Tucker, Robert Alan Jappy; Gammad, Gil Gerald Lasam; Yeo, Yanzhuang; Lei, Zhendong; Zheng, Xiang; Yang, Fengyuan; Ho, John S.; Bolem, Nagarjun; et al.
Abstract: Near‐infrared (NIR) activatable upconversion nanoparticles (UCNPs) enable wireless‐based phototherapies by converting deep‐tissue‐penetrating NIR to visible light. UCNPs are therefore ideal as wireless transducers for photodynamic therapy (PDT) of deep‐sited tumors. However, the retention of unsequestered UCNPs in tissue with minimal options for removal limits their clinical translation. To address this shortcoming, biocompatible UCNPs implants are developed to deliver upconversion photonic properties in a flexible, optical guide design. To enhance its translatability, the UCNPs implant is constructed with an FDA‐approved poly(ethylene glycol) diacrylate (PEGDA) core clad with fluorinated ethylene propylene (FEP). The emission spectrum of the UCNPs implant can be tuned to overlap with the absorption spectra of the clinically relevant photosensitizer, 5‐aminolevulinic acid (5‐ALA). The UCNPs implant can wirelessly transmit upconverted visible light till 8 cm in length and in a bendable manner even when implanted underneath the skin or scalp. With this system, it is demonstrated that NIR‐based chronic PDT is achievable in an untethered and noninvasive manner in a mouse xenograft glioblastoma multiforme (GBM) model. It is postulated that such encapsulated UCNPs implants represent a translational shift for wireless deep‐tissue phototherapy by enabling sequestration of UCNPs without compromising wireless deep‐tissue light delivery. Abstract : Biocompatible upconversion hydrogel implants synergistically conserve the light‐guiding and near‐infrared transducing properties into a wireless light‐delivery implant. Such hydrogel‐based upconversion designs are explored to activate clinically relevant photosensitizer in wireless photodynamic therapy of glioblastoma multiforme. Upconversion implantable is potentially translatable to other phototherapies and as medical implants.